2004
DOI: 10.1021/ja0490830
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Calculation of the 17O NMR Parameters in Ca Oxide and Ca Aluminosilicates:  the Partially Covalent Nature of the Ca−O Bond, a Challenge for Density Functional Theory

Abstract: We apply density functional theory (DFT) to the calculation of the (17)O NMR parameters in Ca and Mg oxides and aluminosilicates. We study the accuracy of the Perdew, Burke, and Ernzerhof (PBE) generalized-gradient approximation to DFT in the description of these systems and the origin of the experimentally observed large dependence of the (17)O chemical shift on the alkaline earth ion. We find that (i) the partially covalent nature of the Ca-O bond has a huge impact on the O chemical shifts. The Ca-O covalenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
236
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(243 citation statements)
references
References 37 publications
6
236
1
Order By: Relevance
“…This value is significantly smaller than for CaO (3.2 eV). 60 This difference can be explained as (i) we used USPP whereas Profeta et al The effect of the shift applied on the 3d orbitals is clearly observed in the conduction band: the energy of the band having mostly a Ca(3d) character is increased and becomes closer to the one obtained using hybrid functional. The band gap stays unchanged (mainly imposed by the position of Ca(4s) states in the conduction band) and is calculated to 6.3 eV using PBE functional.…”
mentioning
confidence: 88%
See 3 more Smart Citations
“…This value is significantly smaller than for CaO (3.2 eV). 60 This difference can be explained as (i) we used USPP whereas Profeta et al The effect of the shift applied on the 3d orbitals is clearly observed in the conduction band: the energy of the band having mostly a Ca(3d) character is increased and becomes closer to the one obtained using hybrid functional. The band gap stays unchanged (mainly imposed by the position of Ca(4s) states in the conduction band) and is calculated to 6.3 eV using PBE functional.…”
mentioning
confidence: 88%
“…In a second step, the correlation between the calculated 19 F σ iso values for 25 twelve binary crystalline compounds and experimental 19 F δ iso values is investigated. A critical problem that was already observed for Ca in oxides 60 is evidenced in fluorides: PBE-DFT (Perdew, Burke and Ernzerhof -Density Functional Theory) method 61 is deficient in describing 3d and 4f localized empty orbitals when considering NMR shielding calculations. To circumvent this problem the Ca, Sc, and La pseudopotentials have been adapted using the methodology described in [60] and a reference calibration curve is proposed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, it is known that the empty Ca 3d-states are too close to the valence band maximum in density functional theory (DFT), resulting in a deviation of the O shift. 39 The fit of Eq. (36) relates the calculated shieldings to chemical shifts from experiment.…”
Section: B Solidsmentioning
confidence: 99%